Cytohistological studies during cotton somatic embryogenesis with brassinosteroid application - (:unkn) unknown (My University, 2010)
0

The histology and chromosome alterations of somatic embryo initiation and development in cotton (Gossypium hirsutum L. cv. Coker) was examined during in vitro exogenous brassinosteroid (BR) application. Calli developed from hypocotyl explants were subjected to 0.5 μM BR. After 10 weeks of calli cultures with somatic embryos at different developmental stages were fixed for histological examinations. The histological examination showed that two types of embryogenic cells induced; epidermal or subepidermal. The embryogenic mass and somatic embryos were mostly derived from several morphologically competent cells from subepidermal cases; however single progenitor cells for epidermal situations. Chromosome behaviour of the cells surrounding embryogenic cells showed abnormal divisions and higher level of polyploidy on BR treated calli when compared to control group.
Keywords: Biyoloji